Selection of a Dominant Negative Retinoblastoma Protein (RB) Inhibiting Satellite Myoblast Differentiation Implies an Indirect Interaction between MyoD and RB - Li, Feng-Qian (American Society for Microbiology, 2000)
Satellite myoblasts serve as stem cells in postnatal skeletal muscle, but the genes responsible for choosing between growth versus differentiation are largely undefined. We have used a novel genetic approach to identify genes encoding proteins whose dominant negative inhibition is capable of interrupting the in vitro differentiation of C2C12 murine satellite myoblasts. The screen is based on fusion of a library of cDNA fragments with the lysosomal protease cathepsin B (CB), such that the fusion protein intracellularly diverts interacting factors to the lysosome. Among other gene fragments selected in this screen, including those of known and novel sequence, is the retinoblastoma protein (RB) pocket domain. This unique dominant negative form of RB allows us to genetically determine if MyoD and RB associate in vivo. The dominant negative CB-RB fusion produces a cellular phenotype indistinguishable from recessive loss of function RB mutations. The fact that the dominant negative RB inhibits myogenic differentiation in the presence of nonlimiting concentrations of either RB or MyoD suggests that these two proteins do not directly interact. We further show that the dominant negative RB inhibits E2F1 but cannot inhibit a forced E2F1-RB dimer. Therefore, E2F1 is a potential mediator of the dominant negative inhibition of MyoD by CB-RB during satellite cell differentiation. We propose this approach to be generally suited to the investigation of gene function, even when little is known about the pathway being studied.